2019
DOI: 10.1111/jfbc.12938
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic evaluation of AMPK/SIRT1/FXR signaling axis, inflammation, and redox status in thioacetamide‐induced liver cirrhosis: The role ofCichorium intybuslinn (chicory)‐supplemented diet

Abstract: Liver cirrhosis is a scene profitable to the advance of hepatocellular carcinoma (HCC). The current work was engrossed to weigh the potential role of Cichorium intybus linn against thioacetamide (TAA)‐induced liver cirrhosis and their probable underlying biochemical and molecular mechanisms. farnesoid‐X‐receptor (FXR) expression, proliferating cell nuclear antigen (PCNA) immunoreactivity, and activated AMP protein kinase (pAMPK), sirtuin‐1 (SIRT1), and interleukin‐6 (IL6) levels were estimated in hepatic tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, AMPK, as an important protein kinase in the process of cell energy metabolism, can regulate Sirt1 activity and reduce the expression of in ammatory genes by activating AMPK, thus inhibiting the in ammatory response [44,45]. In addition, the reported study showed that TST can protect the acute liver injury by inhibiting NF-κB expression [46,47]. More importantly, it was reported that the activation of AMPK/Sirt1 could inhibited MIRI through alleviate in ammation reaction [32][33][34][35], which is very important for MIRI therapy in clinic.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, AMPK, as an important protein kinase in the process of cell energy metabolism, can regulate Sirt1 activity and reduce the expression of in ammatory genes by activating AMPK, thus inhibiting the in ammatory response [44,45]. In addition, the reported study showed that TST can protect the acute liver injury by inhibiting NF-κB expression [46,47]. More importantly, it was reported that the activation of AMPK/Sirt1 could inhibited MIRI through alleviate in ammation reaction [32][33][34][35], which is very important for MIRI therapy in clinic.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it is known that CREB can activate autophagy genes via the Farnesoid X receptor (FXR)/CREB signaling pathway whereby FXR inhibits CREB activation ( 61 63 ). By its turn, AMPK inhibits FXR and thus increases CREB activation ( 64 , 65 ). Regarding BDNF, it was shown that increased levels of BDNF were associated with inhibition of autophagy ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…TAA can induce OS, inflammation, and lipid peroxidation to cause liver damage [ 31 ]. Notably, OS was reported to play an essential role in the pathogenesis of TAA-induced ALI.…”
Section: Discussionmentioning
confidence: 99%